Mandatory Corporate Social and Environment Responsibilities in The New Indonesian Limited Liability Law - Opposunggu, Yu un (Indonesia Law Review, 2011)
On 16 August 2007 President Susilo Bambang Yudhoyono signed the Bill of Limited Liability Company, as approved by the Parliament, and consequently it became the Law No. 40 of Year 2007 regarding Limited Liability Company. The law revokes the then existing Law No. 1 of Year 1995. This law has 14 chapters and 161 articles, and introduces new provision on, inter alia, corporate social and environmental responsibilities (CSER). The legislators have specifically dedicated Chapter V and its Article 74 to this effect. CSER is defined as commitment of the Company to participate in sustainable economic development with the intention of increasing the living quality and beneficial environment for the Company itself, the surrounding communities, and public in general. This article discusses CSER as stipulated in the Law in relation the logic of a limited liability company. It analyzes the necessity of stipulating it in the Law in relation to the objective of a limited liability company.